Evolution of instabilities in filament buckling processes - Monastra, Alejandro Gabriel (2019)
In this work we study the dynamical buckling process of a thin filament immersed in a highly viscous medium. We perform an experimental study to track the shape evolution of the filament during a constant velocity compression. Numerical simulations reproduce the dynamical features observed from the experimental data and allow quantifying the filament's load. We observe that both the filament's load and the wave number evolve in a stepwise manner. In order to achieve a physical insight of the process, we apply a theoretical model to describe the buckling of a filament in a viscous medium. We solve a hydrodynamic equation in terms of normal modes for clamped-clamped boundary conditions and constant applied load. We find a good agreement between experimental data and simulations, suggesting that the proposed mechanistic model captures the essential features underlying the dynamical buckling process.